COMMUNICATION NETWORK MODEL FOR THE FAST REACTION TEAM PROGRAM (TRC) “SARIBATTANG” CHILDREN IN MAKASSAR CITY - Tuti Bahfiarti; Arianto Arianto; Burhanuddin Burhanuddin (Jurnal Inovasi dan Pelayanan Publik Makassar, 2017)
The communication network helps provide the direction and policies of the Quick Response Team (TRC) Program "Saribattang" focus on addressing Social Welfare Problems (PMKS), especially street children, beggars, and sprawl. Rapid Response Team (TRC) "Saribattang" was formed in order to conduct patrol of Social Welfare Persons (PMKS) of Makassar City Social Service. So in the end, reduce PMKS in Makassar City. The research problem is how the operational characteristics and actions, evaluation and sustainability of Saribattang Quick Reaction Team Program for street children and communication network model for sustainability of Saribattang Rapid Response Team Program for street children development in Makassar City. The objectives and targets to be achieved are to understand and describe the characteristics of operational acts and determine the communication activities of street children in the communication network for evaluation and sustainability of the Saribattang Quick Reaction Team Program in the development of street children in Makassar and to find, describe and analyze the model of communication network network) for sustainability of street children development program in Makassar City. For the achievement of objectives and targets are used research methods Mixed-Method research (mixed method research). Methods for obtaining different but complementary data to understand the communication networks formed within the group of street children. The results showed that the non operational street children in Makassar is a complex social problem phenomenon. This phenomenon occurs in the community due to disruption of social functions, said to be disturbed because the child should be in a home situation, school or play environment in which there are interactions that support the child's development, whether physical, motor, social, psychological and moral. Such conditions can not be met by street children. They are required to work on the streets, the operational act they do it refers to the search for extra money, help parents and asked the family. Consideration of policies and strategies of "Innovation Desensitization" (acts of innovation through the development of communication and information) on the target group or individual street children through the communication network leader utilization approach among them. The role of opinion leaders to solve various problems of street children in their group communication networks. Especially in support of Fast Response Team (TRC) “Saribattang” in coaching street children in Makassar City. Establish interpersonal communication approach in integrated communication network. Aiming at the Social Service through Quick Response Team (TRC) Saribattang and street children in Makassar together open themselves in evaluating the successful implementation of programs directly. Model of communication network formation in order to facilitate information dissemination process or program of Quick Reaction Team (TRC) Saribattang in coaching street children in Makassar City. The program does not focus on street children alone but also on the family and other significance of the street children themselves.